Exporting Legality - Mariya Tait Slys (Graduate Institute Publications, 2014)
How did two radically different legal cultures, those of the Ottomans and the Chinese, gradually acquire a legal architecture analogous to that of Europe? This Paper attempts to answer this question by providing a comparative study in legal history of the rise and demise of extraterritorial consular jurisdiction, utilizing a post-colonial and inter-disciplinary approach to international law. The study reveals that the establishment of consular jurisdiction during the nineteenth century was cl...